2005
DOI: 10.1007/s00586-005-0003-x
|View full text |Cite
|
Sign up to set email alerts
|

Adjacent level discitis after anterior cervical discectomy and fusion (ACDF): a case report

Abstract: This report describes a case of spondylodiscitis occurring adjacent to levels at which anterior cervical discectomy and fusion was performed. The objective is to describe a rare cause of spondylodiscitis and discuss its successful management. Post-operative discitis involving the same level is a known occurrence. We report an interesting case of spondylodiscitis occurring at the adjacent level of fusion, and to our knowledge this is the first such case reported in literature. A two-level decompression and fusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 9 publications
1
26
0
Order By: Relevance
“…Various organ culture systems have been in development and use: (1) culture of discs without endplates (Chiba et al, 1998), (2) with vertebral bone (Lee et al, 2006;IllienJunger et al, 2010;Chan and Gantenbein-Ritter, 2012b) and (3) with cartilaginous endplates Jim et al, 2011). Organ culture systems except for those retaining only the cartilaginous endplate model were unable to maintain high cell viability even for short durations of culture; whereas the cartilaginous endplate model for human disc culture developed by us has overcome this problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various organ culture systems have been in development and use: (1) culture of discs without endplates (Chiba et al, 1998), (2) with vertebral bone (Lee et al, 2006;IllienJunger et al, 2010;Chan and Gantenbein-Ritter, 2012b) and (3) with cartilaginous endplates Jim et al, 2011). Organ culture systems except for those retaining only the cartilaginous endplate model were unable to maintain high cell viability even for short durations of culture; whereas the cartilaginous endplate model for human disc culture developed by us has overcome this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond Thompson grade 3, surgical treatment would be the mainstay treatment due to severely depleted cell population and the disrupted integrity of the disc. Link-N therapy thus may not be able to repair higher grades of degeneration where annular fissures and tears are present, although it could be used post-surgery to delay adjacent level disc disease (Kulkarni and Hee, 2006;Lund and Oxland, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…27,30 Application of a cervical plate has gained acceptance as a means of increasing fusion rates and preventing graft dislodgement, but it can be expensive and has been associated with complications such as dysphagia, infection, and instrumentation failure. 4,13,23,24 Instrumented fusion is also associated with a significantly higher amount of intraoperative blood loss when compared with procedures in which plate fixation is not used. 31 The effectiveness of plate fixation in single-level ACDF is controversial, and there are significant differences in fusion rates among published studies.…”
Section: Discussionmentioning
confidence: 99%
“…Kulkarni et al [24] reported a case of adjacent level discitis after anterior cervical discectomy and fusion, and the radiographs showed segmental C4-C5 kyphosis, decreased disc height at this level with erosion of end-plates, halo around the screws and enlarged prevertebral soft tissue shadow. MRI showed discitis at the C4-C5 level with prevertebral and epidural abscesses from C4-C6.…”
Section: Imaging Studiesmentioning
confidence: 99%
“…Kulkarni et al [24] reported a case of adjacent level discitis after anterior cervical discectomy and fusion and the perioperative biopsy was positive for Serratia marcescens.…”
Section: Postoperative Pyogenic Spondylodiscitismentioning
confidence: 99%